Testing the 'brain gain' hypothesis: Micro evidence from Cape Verde - Cátia Batista; Aitor Lacuesta; Pedro C. Vicente (Institute for the Study of Labor (IZA), 2010)
Does emigration really drain human capital accumulation in origin countries? This paper explores a unique household survey purposely designed and conducted to answer this research question. We analyze the case of Cape Verde, a country with allegedly the highest 'brain drain' in Africa, despite a marked record of income and human capital growth in recent decades. Our micro data enables us to propose the first explicit test of 'brain gain' arguments according to which the prospects of own future migration can positively impact educational attainment. According to our results, a 10pp increase in the probability of own future migration may improve the average probability of completing intermediate secondary schooling by 8pp for individuals who do not migrate before age 16. Strikingly, this same 10pp increase may raise the probability of completing intermediate secondary schooling by 11pp for an individual whose parents were both non migrants when the educational decision was made. Our findings are robust to the choice of instruments and econometric model. Overall, we find that there may be substantial human capital gains from lowering migration barriers.
Keywords: F22; J24; O12; O15; 330; Brain drain; brain gain; international migration; human capital; effects of emigration in origin countries; household survey; Cape Verde; sub-Saharan Africa; Internationale Wanderung; Brain Drain; Humankapital; Wohlfahrtseffekt; Kap Verde